Using the phantom 4 RTK drone for photogrammetry to create topographic plan of road - El Atiq Jaouad; El Harti Abderrazak (E3S Web of Conferences)
Drone photogrammetry is a swift, inexpensive, accurate, and detailed procedure that makes it possible to obtain pictures for the creation of a high spatial resolution Digital Terrain Model (DTM) with enhanced planimetric and altimetric precision. It also provides the possibility of cartographic land use. Study site: the experiment was carried out in a mountain area using a Phantom 4 RTK drone over the road connecting Demnate to Aït Bouguemez in the province of Azilal. The results were processed with Agisoft software running a TIN (Triangulated Irregular Network) based algorithm for a geometric classification (ground vs above ground). This was followed by manual intervention to increase the accuracy of the desired output. Image processing and classification helped to build a Digital Terrain Model with an altimetric RMSE of 5 cm - just 3 cm for planimetric error. This extreme accuracy is valuable when performing tasks that demand great precision, like building a detailed road development plan.Drone photogrammetry excels in the development of roads, highway, and many other tasks mainly thanks to its speed, cost-effectiveness and detail. In this paper, the results show that this technique produces high- fidelity images and can make a DTM with high precision. This higher accuracy leads to informed decisions in the planning and implementation of road work.